Monkey’s hand in corn in the central and western regions of Mexico - Márquez-Diego, José Jesús; Ochoa-Martínez, Daniel Leobardo; Rojas-Martínez, Reyna Isabel; Rodríguez-Maciel, J. Concepción; Nava-Díaz, Cristian; Sánchez-Pale, José Ricardo (Revista Mexicana de Ciencias Agrícolas, 2024)
Monkey’s hand is a disease that reduces the yield of corn grain. Its distribution is nationwide, and its etiology has not been determined. It is considered that the use of genetically tolerant germplasm is the only effective way to manage this phytosanitary problem. Therefore, this work aimed to evaluate its incidence in corn-growing regions and the tolerance of the materials available in Mexico. In the 2023 autumn-winter cycle, the incidence of this disease was evaluated in function of the altitude above mean sea level in commercial plots in the States of Mexico, Jalisco, Nayarit, Querétaro, San Luis Potosí, Zacatecas, Michoacán, and Guanajuato. Plants with symptoms were found in all evaluated states, with incidences of up to 96%. Native varieties had a greater incidence (38.15%) than improved ones (6.47%). A positive covariance and a highly significant correlation (r-42.32%) were detected between the incidence and altitude variables.
Keywords: ‘bouquet ears’; diseases in corn; ‘mano de chango’; proliferation